2008
DOI: 10.1158/0008-5472.can-07-1589
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Inducible Factor-1 Target Genes as Indicators of Tumor Vessel Response to Vascular Endothelial Growth Factor Inhibition

Abstract: Antiangiogenic therapy improves survival in patients with advanced stage cancers. Currently, there are no reliable predictors or markers for tumor vessel response to antiangiogenic therapy. To model effective antiangiogenic therapy, we disrupted the VEGF gene in three representative cancer cell lines. HCT116 xenografts had low proportions of endothelial tubes covered by pericytes that stained with A-smooth muscle actin (SMA) antibody. Upon disruption of VEGF, HCT116 VEGFÀ/À xenografts had significantly decreas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 36 publications
7
42
1
2
Order By: Relevance
“…6B). These changes in LDH activity and lactate concentration were consistent with an increase in hypoxia in the LoVo tumors (29,41). There was no change in fumarase activity from the pretreatment level of 0.40 AE 0.04 mmole/min/mg protein (Fig.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…6B). These changes in LDH activity and lactate concentration were consistent with an increase in hypoxia in the LoVo tumors (29,41). There was no change in fumarase activity from the pretreatment level of 0.40 AE 0.04 mmole/min/mg protein (Fig.…”
Section: Resultssupporting
confidence: 73%
“…In this preclinical study, we sought to detect early metabolic and vascular changes induced by bevacizumab treatment in 2 colorectal cancer xenograft models with differential sensitivity to VEGF blockade. LoVo tumors display a higher dependence on VEGF, with greater vessel permeability (31) and lower vessel pericyte coverage (29) than HT29 tumors, therefore upon VEGF blockade will exhibit reduced MVD and perfusion, along with marked expansion of hypoxic regions (29). Conversely, HT29 tumor cells are less sensitive to VEGF Figure 4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, microscopic studies have revealed the nearly ubiquitous presence of pericytes on tumor vessels, although such pericytes are more loosely attached to the vasculature and at reduced density compared with respective normal tissues (25,(43)(44)(45). Different cancer cells exhibit dramatically varying pericyte coverage when transplanted to form tumor xenografts (46). In our study, DCIS cell-derived tumor xenografts had very few pericytes whereas blood vessels in neuT tumors were well covered by pericytes ( Figure 7A and Supplemental Figures 1B and 8).…”
Section: Methodsmentioning
confidence: 54%
“…However, survival benefits are observed only in a subset of patients, as a significant number of patients show only modest response presumably because of intrinsic or rapidly acquired resistance to antiangiogenic therapy (14). One proposed mechanism of resistance to antiangiogenic agents is the onset of hypoxia within the tumor as a result of vessel regression during the course of antiangiogenic therapy (15,16). Moreover, effective inhibition of neovascularization using antiangiogenic therapy was shown in some cases to change the phenotype of tumors by increasing their invasion and metastatic potential (17).…”
Section: Introductionmentioning
confidence: 99%